2021
DOI: 10.1186/s12544-021-00481-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping travel behavior changes during the COVID-19 lock-down: a socioeconomic analysis in Greece

Abstract: Background COVID-19 pandemic is a challenge that the world had never encountered in the last 100 years. In order to mitigate its negative effects, governments worldwide took action by prohibiting at first certain activities and in some cases by a countrywide lockdown. Greece was among the countries that were struck by the pandemic. Governmental authorities took action in limiting the spread of the pandemic through a series of countermeasures, which built up to a countrywide lockdown that lasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…The sample had a small percentage of respondents who were over 40 years old (1.43%). This probably happened because older people do generally have fewer digital competencies and they would be more reluctant to participate in an online survey (Politis et al, 2021). Moreover, people who are over 60 years old are already retired and/or rarely use public transport due to certain psy- cho-social barriers which have been identified both in Italy (Mariotti,et al,2021) and in other countries (Al-Rashid et al, 2021).…”
Section: Data Collectionmentioning
confidence: 99%
“…The sample had a small percentage of respondents who were over 40 years old (1.43%). This probably happened because older people do generally have fewer digital competencies and they would be more reluctant to participate in an online survey (Politis et al, 2021). Moreover, people who are over 60 years old are already retired and/or rarely use public transport due to certain psy- cho-social barriers which have been identified both in Italy (Mariotti,et al,2021) and in other countries (Al-Rashid et al, 2021).…”
Section: Data Collectionmentioning
confidence: 99%
“…Countermeasures against the diffusion of COVID-19 had a significant impact on mobility [1,12,13,19] because of direct limitations or bans on transport services, forbidden trips, the closure of activities, as well as self-imposed individual restrictions [20]. Many authors reported significant changes in users' travel habits worldwide [7,8,21,22], with variations in the frequency of trips, travel purposes and modal split [12], which may have varied in accordance with country-specific factors [23,24] and socio-economic characteristics of citizens [25]. As regards European nations, comparing trip statistics before and after the pandemic: in Germany, about 60% of persons changed transport mode [14], in particular, the number of people performing monomodal trips rose from 68% to 83% [26]; in Greece, the average number of daily trips decreased by 50% [12]; in the Netherlands, about 80% of people reduced their out-of-home activities and the number of trips decreased by 55% compared to 2019 [9]; in Poland, 50% of people reduced their travel time by more than two thirds [20]; commuting trips dropped by 80% in Spain [13]; in Italy, the number of people reporting no daily trips increased by 27% [24] and the number of internal trips decreased by 50% [27,28], while commuting trips were reduced by 69% [8]; even in Sweden, where restrictions were voluntary, 86% of the population changed their commuting trips with 66% of people who commuted for 5 days a week prior to the pandemic deciding not to travel [29].…”
Section: Introductionmentioning
confidence: 99%
“…Irawan et al [46] developed a structural equation model to analyse variations in activity and travel behaviour after the COVID-19 outbreak in Indonesia. Politis et al [12,25] applied a generalized linear model and ordinary-least squares regressions to predict trip frequency and duration in Greece. Scorrano and Danielis [17] modelled mode choice before and during the COVID-19 pandemic using revealed-preferences and stated-preferences data from an Italian city.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pandemic outbreak has posed great challenges to society, triggering important changes in living and mobility patterns that are necessary to understand. The changes brought about by the pandemic worldwide have been addressed through different perspectives [12][13][14][15]. Indeed, transport and city planning need to address all these issues through a comprehensive perspective to assure a sustainable and inclusive recovery.…”
Section: Introductionmentioning
confidence: 99%